Community-based early childhood development centers as a platform to promote as a platform to promote production and consumption diversity in Malawi - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
The World Bank and the Government of Malawi agreed in June 2018 to scale-up a nutrition-sensitive intervention based on results from an IFPRI-led impact evaluation which showed that preschools can be an effective platform for delivering a nutrition-sensitive agricultural intervention. This will start in 2019.